Alaska and adjoining territory / drawn by H. Lindenkohl - United States Coast Survey (U.S. Coast Survey, 1869, 1869)
Shows Alaska and western Yukon Territory. "The Yukon River, ranges of mountains, shores of Norton Sound and many features of the interior from a reconnaissance by W.H. Dall, Director of the Scientific Corps, of the W.U. Tel Expedition, 1865-1868." Cover title: Alaska. Relief shown by hachures. Depths shown by soundings. Map dissected and mounted on cloth backing. Inset: Aleutian Islands. "No. 20"--Upper right margin. Color 1:3,421,440